A Modified Hestenes-Stiefel Conjugate Gradient Method and its Global convergence for unconstrained optimization - Al-Naem, Ghada (Iraqi Journal of Science, 2023)
In this paper, we proposed a modified Hestenes-Stiefel (HS) conjugategradient method. This achieves a high order accuracy in approximating the secondorder curvature information of the objective function by utilizing the modifiedsecant condition which is proposed by Babaie-Kafaki [1], also we derive a nonquadraticconjugate gradient model. The important property of the suggestionmethod that is satisfy the descent property and global convergence independent ofthe accuracy of the line search. In addition, we prove the global convergence undersome suitable conditions, and we reported the numerical results under theseconditions.